Proceedings of the 23rd ACM/IEEE International Conference on Model Driven Engineering Languages and Systems: Companion Proceedi 2020
DOI: 10.1145/3417990.3419226
|View full text |Cite
|
Sign up to set email alerts
|

Validity frame concept as effort-cutting technique within the verification and validation of complex cyber-physical systems

Abstract: The increasing performance demands and certification needs of complex cyber-physical systems (CPS) raise the complexity of the engineering process, not only within the development phase, but also in the Verification and Validation (V&V) phase. A proven technique to handle the complexity of CPSs is Model-Based Design (MBD). Nevertheless, the verification and validation of complex CPSs is still an exhaustive process and the usability of the models to front-load V&V activities heavily depends on the knowledge of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
(17 reference statements)
0
2
0
Order By: Relevance
“…Van Mierlo et al 10 proposed the essential and conceptual, yet practical, structure of the VF concept, together with a process for building them. In Van Acker and colleague's studies, [32][33][34] VFs are demonstrated in different engineering activities, showing the benefits of using them within a verification and validation (V&V) activity, a computational design synthesis (CDS) activity, and a digital twin design activity.…”
Section: Related Workmentioning
confidence: 99%
“…Van Mierlo et al 10 proposed the essential and conceptual, yet practical, structure of the VF concept, together with a process for building them. In Van Acker and colleague's studies, [32][33][34] VFs are demonstrated in different engineering activities, showing the benefits of using them within a verification and validation (V&V) activity, a computational design synthesis (CDS) activity, and a digital twin design activity.…”
Section: Related Workmentioning
confidence: 99%
“…This includes, for example, SCADE [5] or TargetLink [19]. Furthermore, there are many approaches to facilitate the use of models in the safety-critical area via subsequent formal verification and validation [20] [21] of models and requirements through model-checking [22] [23] [24]. In addition to a model checker, the UPPAAL tool also offers the possibility of creating abstract models, simulate dynamic behavior, and specify and verify the safety of the models [25] [26].…”
Section: Related Workmentioning
confidence: 99%